Different treatment of the femoral neck fractures - Saveski A; Trajanovski A; Karapandzevska S; Gjorgjievska K; Bozinovska B; Manasieva M; Georgieva D (Faculty of Physical Education, Sport and Health, Skopje, Republic of Macedonia, 2022)
The incidence of femoral neck fractures is increasing steadily and daily. The main reason for this data both in the literature and our country is the increase in the life expectancy of the population and the sophistication of medical implants. These fractures are one of the most significant causes of mortality and morbidity in elderly population. In almost all cases, these fractures lead to exacerbation of existing chronic diseases and as a result lead to deterioration, i.e. reduced function of the locomotor system and failure of other organ systems, which often leads to death. They are not only a hospital and health problem, but a socio-economic and financial one too, as for their treatment significant financial resources are spent which additionally burden the health funds. A fracture of the femoral neck can be a trigger for a series of health problems that require different levels of care. The options for surgical treatment for this type of fractures include 2 concepts, namely surgical fixation and arthroplasty. A number of surgical techniques are still controversial and are subject of discussion and investigation